EVALUASI PENERAPAN PRINSIP AKUNTANSI SUBSTANSI MENGUNGGULI BENTUK FORMAL PADA STANDAR AKUNTANSI PEMERINTAH OLEH BPK PERWAKILAN PROVINSI SULAWESI UTARA TERHADAP PEMERIKSAAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Siregar, Maruli Harry; Nangoi, Grace B.; Kalangi, Lintje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
This study used a qualitative method of ethnography aimed Evaluation Accounting Principles Substance Over Form Formal perform On Government Accounting Standards By BPK Representative Province of North Sulawesi on Auditing of Local Government Finance Statement. Data collected by interviews and observations of key informants comprising five LKPD team leader. The results showed that the examiner shows sometimes there are variations in interpreting the six cases of substance over form in government accounting standards in the auditing of financial statements of the government. The lack of common ground in the assessment of the examiner, showed that in accounting principles-based approach to standard setting which assumes that the professional judgment by the examiner is uniform on each examination is a very difficult thing to do. It can affect the implementation of the tasks inspectors in carrying out the examination of financial statements of the government.